A SOLAR RADIATION PREDICTION MODEL FOR APPLICATIONS IN ENERGY HARVESTING - ABDUL GHAFOOR, MUHAMMAD HAFIDZ (Universiti Teknologi PETRONAS, 2016)
Solar energy, the most abundant energy resource on earth as well as it is the most evenly distributed energy resource. The intensity varies since the beginning of the rise of sun to noon and until sunset shows that solar radiation is intermittent in nature. Solar radiation also is an unpredictable source as well due to changing in weather such as raining, hot, dust, and cloud cover. Because of this, before the installation of Solar Energy Harvesting system, we need an information of the solar radiation at a particular area to achieve an optimal performance. This report will present the MATLAB based for hourly solar radiation prediction model. The existing data will be used to calculate some information to get the parameters for predicting the solar radiation. At first, a daily solar radiation is predicted. Then, it comes down to predict an hourly solar radiation prediction. This report also will compare the measured value and the predicted value to find the accuracy. There will be some modification to the existing formula to achieve higher accuracy of predicting solar radiation.